Shufeng Jiedu capsules for treating acute exacerbations of chronic obstructive pulmonary disease: a systematic review and meta-analysis - Ru-yu Xia; Xiao-yang Hu; Yu-tong Fei; Merlin Willcox; Ling-zi Wen; Ming-kun Yu; Li-shan Zhang; Meng-yuan Dai; Guang-he Fei; Mike Thomas; Nick Francis; Tom Wilkinson; et al. (BMC, 2020)
Abstract Background Chinese herbal medicine is widely used in combination with usual care for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) in China. Chinese patent medicine Shufeng Jiedu (SFJD) capsules is widely used for respiratory infectious diseases. This review aims to evaluate effectiveness and safety of SFJD for AECOPD. Methods A systematic review of randomised controlled trials (RCTs) in patients with AECOPD, who received SFJD as a single intervention or as add-on treatment to usual care. PubMed, the Cochrane Library, EMBASE, Scopus, Web of Science and four Chinese databases were searched from inception to April 2019. Two authors screened trials, extracted data, and assessed risk of bias, independently. Meta-analysis was performed using RevMan 5.3 software. We performed subgroup analyses and sensitivity analyses according to the predefined protocol. Quality of evidence was assessed using GRADE. Results Thirteen RCTs (1036 patients, with 936 inpatients) were included, all compared SFJD in combination with usual care (including antibiotics) to usual care alone. The mean age of participants ranged from 52 to 67 years, with approximately 60% male. Due to lack of blinding and other factors, all trials were of high risk of bias. SFJD was associated with a significant reduction in treatment failure, from 20.1 to 8.3% (11 trials; 815 patients; relative risk 0.43, 95% confidence interval [CI] 0.30 to 0.62), and duration of hospital stay (2 trials; 79 patients; mean difference − 4.32 days, 95% CI − 5.89 to − 2.75 days). No significant difference in adverse events was found between SFJD and control groups. Conclusion Low certainty evidence suggests SFJD may bring additional benefit in reducing treatment failure, shorten hospital stay, and improving symptoms. Further large, high quality RCTs are needed to confirm its benefit and safety. Trial registration PROSPERO CRD42019133682 .